Analisis Fundamental Nilai Intrinsik Dan Nilai Pasar Saham Sebagai Alat Bantu Dalam Pengambilan Keputusan Investasi - Yuliansyah Yuliansyah; I Ketut Sukedarsana (Jurnal Ilmiah ESAI, 2007)
The purpose of this research is to describe fundamental analysis with price earning ratio approach as a decision making tool of shares at fund market. The samples which are used in this research are 16 companies.  Hypothesis on this research is there is no significant different between intrinsic value and shares market value that notified with Ho and there is significant different between intrinsic values and shares price value that notified with Ha.  The criterion of the test is compared between Z test value and Z table. The research showed that the companies which have shares market price that lower than intrinsic value are 5 of 16 companies or 31, 25. The rest, 11 of 16 companies or 68, 75%, is vice versa. By using Wilcoxon signed rank test t method, Z-test is 2,023 to shares market price < intrinsic value and Z-value was 1, 96 (a = 0, 05). As 2,023 and 2,934 > 1,96,  it is concluded that Ho is rejected and Ha is accepted that means that there is significantly different between shares market price and intrinsic value, so that it will be usefull for investor as a decision making at money market. Kata Kunci :  investasi, nilai intrinsik, nilai pasar saham.